Genome-Wide Identification of Calcium Dependent Protein Kinase Gene Family in Plant Lineage Shows Presence of Novel D-x-D and D-E-L Motifs in EF-Hand Domain - Mohanta, Tapan K.; Mohanta, Nibedita; Mohanta, Yugal K.; Bae, Hanhong (Frontiers in Plant Science, 2015)
Calcium ions are considered ubiquitous second messengers in eukaryotic signal transduction pathways. Intracellular Ca2+ concentration are modulated by various signals such as hormones and biotic and abiotic stresses. Modulation of Ca2+ ion leads to stimulation of calcium dependent protein kinase genes (CPKs), which results in regulation of gene expression and therefore mediates plant growth and development as well as biotic and abiotic stresses. Here, we reported the CPK gene family of 40 different plant species (950 CPK genes) and provided a unified nomenclature system for all of them. In addition, we analyzed their genomic, biochemical and structural conserved features. Multiple sequence alignment revealed that the kinase domain, auto-inhibitory domain and EF-hands regions of regulatory domains are highly conserved in nature. Additionally, the EF-hand domains of higher plants were found to contain four D-x-D and two D-E-L motifs, while lower eukaryotic plants had two D-x-D and one D-x-E motifs in their EF-hands. Phylogenetic analysis showed that CPK genes are clustered into four different groups. By studying the CPK gene family across the plant lineage, we provide the first evidence of the presence of D-x-D motif in the calcium binding EF-hand domain of CPK proteins.